Tetrahydrofolate and other growth requirements of certain strains of Ruminococcus flavefaciens. - Slyter, L L (1977)
Two strains of Ruminococcus flavefaciens were studied. Each grew in a chemically defined minimal medium containing: minerals; ammonium sulfate as a nitrogen source; amino acids as a nitrogen source, a growth promotant(s) or as both; cellobiose as an energy and carbon source; isobutyric acid, isovaleric acid, carbonic acid, and bicarbonate as additional carbon sources; and biotin, thiamine, and tetrahydrofolic acid as vitamins. Tetrahydrofolic acid (5 ng/ml) served as a replacement for rumen fluid that was required in previous media tested for the growth of these bacteria. The present bacteria differ from many of the ruminococci previously studied in that they do not require either p-amino-benzoic acid or folic acid but do require tetrahydrofolic acid for maximum growth. Dihydrofolic acid and 5-methyltetrahydrofolic acid can substitute for tetrahydrofolic acid in minimal chemically defined medium. Thus, there must be extensive metabolic interaction between the microbes inhabitating the rumen, because the R. flavefaciens isolated had complex requirements for growth and yet was among the predominant bacteria in the rumen of cattle fed a simple vitamin B-deficient, nonprotein nitrogen, high-fiber, purified diet.